The Bahamas : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The article highlights the economic condition, fiscal policies, external stability, and financial growth strategy of The Bahamas. The economy of The Bahamas showed gradual growth of about 2.5 percent by 2012, but there were challenges for the country. The nation has to rebuild macroeconomic buffers against external imbalances, regulate nonperforming loans, reduce unemployment, and increase the business sector. This assessment is an analysis of The Bahamas' recent development and forthcoming plans to encounter global threats.